Analisis Kadar Vitamin A, C dan E pada Biskuit dari Formulasi Tepung Labu Siam (Sechium edule) dan Tepung Kacang Hijau (Vigna radiata L.) - Reynaldi Tandi; Sri Hastuti; Tahril Tahril; Sri Mulyani (JURNAL BANUA OGE TADULAKO, 2021)
Chayote and green beans are classified as plants that contain various vitamins. Vitamins in the human body can function as antioxidants and metabolic regulators. Management of chayote and green beans into flour is still not implemented. This study aims to determine the levels of vitamins A, C and E contained in biscuits from the formulation of chayote flour and mung bean flour. Determination of levels of vitamins A, C and E in biscuits using UV-Vis spectrophotometric method. The results of this study indicate that biscuits with a ratio of 0:100% (0:200 grams) contain 0.0063 mg/100g of vitamin A, 12.740 mg/100g of vitamin C and 0.0026 mg/100g of vitamin E; a ratio of 25:75% (50:150 grams) containing 0.0044 mg/100g of vitamin A, 13,406 mg/100g of vitamin C and 0.0019 mg/100g of vitamin E; a ratio of 50:50% (100:100 grams) containing 0.0038 mg/100g of vitamin A, 14,826 mg/100g of vitamin C and 0.0033 mg/100g of vitamin E; a ratio of 75:25% (150:50 grams) containing 0.0071 mg/100g of vitamin A, 15.397 mg/100g of vitamin C and 0.0040 mg/100g of vitamin E; the ratio of 100:0% (20:0 gram) contains 0.0046 mg/100g of vitamin A, 14,258 mg/100g of vitamin C and 0.0039 mg/100g of vitamin E. The results of this study are expected to help the community in cultivating and processing chayote and green beans into biscuit flour which is rich in vitamin content.